Antagonistic game design: The author as a player - Gualeni, Stefano (Eludamos: Journal for Computer Game Culture, 2025)
This article examines a particular relationship between game authors and players: the possibility for game authors to co-opt the role of players in the very game they created. Among the various ways in which this can occur, the article concentrates on ‘antagonistic game design’: the creation of games meant to frustrate and provoke their players. Player engagement, I argue, does not solely arise from the pleasure of overcoming in-game obstacles, participating in the unfolding of the game’s narrative or defeating other players, but can also emerge from resisting and opposing an imagined persona: the off-putting and often sadistic (implied) author behind the work. By projecting an unsympathetic and adversarial attitude towards players, antagonistically designed games can establish an asynchronous adversarial relationship with them and foster distinctive avenues for meaning-making and the self-validation of players.